Hepatobiliary scintigraphy findings of a patient with polianomaly presenting with icterus - Koç, Zehra Pinar; Balci, Tansel Ansal; Kepenek, Ferhat (BMJ Publishing Group, 2011)
17-days-old baby girl with continuous crying and persistent icterus attended to our hospital. Hepatobiliary scintigraphy was performed in order to diagnose aetiology of icterus and polianomaly of patient was incidentally found with scintigraphic imaging. Copyright 2011 BMJ Publishing Group. All rights reserved.
Keywords: abdominal radiography; accessory spleen; article; ascites; bile duct atresia; biopsy technique; cardiography; case report; clinical feature; computer assisted tomography; congenital malformation; crying; dextrocardia; differential diagnosis; female; follow up; hepatobiliary scintiscanning; hepatomegaly; human; human tissue; hyperbilirubinemia; infant; laboratory test; leukocytosis; liver disease; newborn hepatitis; newborn jaundice; outcome assessment; physical examination; priority journal; thrombocytosis